A modified regimen of rituximab in pemphigus: A retrospective study - Tanvi Pradeep Vaidya; Jacintha Martis; Ramesh M Bhat; Sukumar Dandekeri (Wolters Kluwer Medknow Publications, 2020)
Introduction: Rituximab is a chimeric monoclonal antibody targeted against CD20 T-cells. It acts by the destruction of autoreactive B-cells. It is a common biologic agent widely used for the treatment of B-cell lymphoma, lymphoproliferative disorders, and inflammatory conditions that are refractory to conventional treatment, such as rheumatoid arthritis. However, various recent studies have shown an increasing number of serious adverse events associated with the use of rituximab, such as serious, often fatal, infusion reactions, infections, rigors, fever, peripheral edema, hypertension, myelosuppression, elevated transaminases, and cardiac failure. Only a few such studies have been performed in Indian patients, where Rituximab is still a new molecule. Aims: The aim of this study is to assess the efficacy and adverse events profile in patients with pemphigus group of diseases treated with rituximab. Materials and Methods: In this retrospective study, we analyzed records of 20 cases of pemphigus who received a modified rheumatoid arthritis (RA) protocol from January 2016 to June 2018, for the efficacy of rituximab as well as for the immediate and late adverse effects encountered with the use of rituximab. Results: It was found that 50% of cases achieved complete remission for the entire duration of follow up. The mean duration of remission was 8.55 months. More than 75% of patients relapsed only after 6 months. Twelve patients (60%) had various infusion reactions such as fever, chills, giddiness, breathlessness, bradycardia, and cyanosis. About 30% of the patients developed late side effects such as onychomycosis and sepsis. One of the patients died due to sepsis. Conclusions: Hence, we conclude that rituximab is still very effective at half the dose in the conventional RA protocol, and although it is a highly efficacious drug, it must be used with great caution, keeping in mind, these catastrophic side effects.